Note Purchase Agreement Between the People's Bank of China and the International Monetary Fund. (Policy Papers; Policy Paper ;, 2009)
In light of the international effort to ensure the adequacy of the financial resources available to the Fund, and with a view to supporting the Fund's ability to provide timely and effective balance of payments assistance, particularly to developing and emerging market countries affected by the global financial crisis, the PBC agrees to purchase from the Fund promissory notes.